Multiple Cationic Amphiphiles Induce a Niemann-Pick C Phenotype and Inhibit Ebola Virus Entry and Infection - Shoemaker, Charles J.; Schornberg, Kathryn L.; Delos, Sue E.; Scully, Corinne; Pajouhesh, Hassan; Olinger, Gene G.; Johansen, Lisa M.; White, Judith M. (PLOS ONE, 2013)
Ebola virus (EBOV) is an enveloped RNA virus that causes hemorrhagic fever in humans and non-human primates. Infection requires internalization from the cell surface and trafficking to a late endocytic compartment, where viral fusion occurs, providing a conduit for the viral genome to enter the cytoplasm and initiate replication. In a concurrent study, we identified clomiphene as a potent inhibitor of EBOV entry. Here, we screened eleven inhibitors that target the same biosynthetic pathway as clomiphene. From this screen we identified six compounds, including U18666A, that block EBOV infection (IC50 1.6 to 8.0 µM) at a late stage of entry. Intriguingly, all six are cationic amphiphiles that share additional chemical features. U18666A induces phenotypes, including cholesterol accumulation in endosomes, associated with defects in Niemann–Pick C1 protein (NPC1), a late endosomal and lysosomal protein required for EBOV entry. We tested and found that all six EBOV entry inhibitors from our screen induced cholesterol accumulation. We further showed that higher concentrations of cationic amphiphiles are required to inhibit EBOV entry into cells that overexpress NPC1 than parental cells, supporting the contention that they inhibit EBOV entry in an NPC1-dependent manner. A previously reported inhibitor, compound 3.47, inhibits EBOV entry by blocking binding of the EBOV glycoprotein to NPC1. None of the cationic amphiphiles tested had this effect. Hence, multiple cationic amphiphiles (including several FDA approved agents) inhibit EBOV entry in an NPC1-dependent fashion, but by a mechanism distinct from that of compound 3.47. Our findings suggest that there are minimally two ways of perturbing NPC1-dependent pathways that can block EBOV entry, increasing the attractiveness of NPC1 as an anti-filoviral therapeutic target.